2016
DOI: 10.3390/ma9020094
|View full text |Cite
|
Sign up to set email alerts
|

How to Study Thermal Applications of Open-Cell Metal Foam: Experiments and Computational Fluid Dynamics

Abstract: This paper reviews the available methods to study thermal applications with open-cell metal foam. Both experimental and numerical work are discussed. For experimental research, the focus of this review is on the repeatability of the results. This is a major concern, as most studies only report the dependence of thermal properties on porosity and a number of pores per linear inch (PPI-value). A different approach, which is studied in this paper, is to characterize the foam using micro tomography scans with smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 85 publications
1
29
0
Order By: Relevance
“…Although the surface/volume ratio of foams is one of the most relevant parameters for the control of their process performances, the effective evaluation of this property is still subject to a significant uncertainty . Several experimental techniques are available for the measurement of the specific surface area of the support: a conventional approach widely used in catalysis is the Brunauer‐Emmett‐Teller (BET) measurement of nitrogen physisorption ; however, this method has been criticized by several authors because it tends to overestimate the surface area of the support , . Magnetic resonance imaging (MRI) has been adopted by several authors for the imaging of ceramic supports , .…”
Section: Introductionmentioning
confidence: 99%
“…Although the surface/volume ratio of foams is one of the most relevant parameters for the control of their process performances, the effective evaluation of this property is still subject to a significant uncertainty . Several experimental techniques are available for the measurement of the specific surface area of the support: a conventional approach widely used in catalysis is the Brunauer‐Emmett‐Teller (BET) measurement of nitrogen physisorption ; however, this method has been criticized by several authors because it tends to overestimate the surface area of the support , . Magnetic resonance imaging (MRI) has been adopted by several authors for the imaging of ceramic supports , .…”
Section: Introductionmentioning
confidence: 99%
“…(28)). However, Schampheleire et al [6] observed that the a sf values estimated using Eq. (27) by Calmidi and Mahajan [63] deviates seriously from those obtained experimentally through a µCT scan with differences up to 233%, while the model of Fourie and Du Plessis [49] performs much better with up to 22% deviation from the experimental data of the full µCT scan.…”
Section: Solid-fluid Interstitial Thermal Exchange Within Open-cell Mmentioning
confidence: 99%
“…After metal solidification, the spheres are dissolved through washing them simply with water. Using this casting technique results in foams having more uniformly spherical-shaped cells unlike those formed by the investment casting, as shown in Figure 2 (De Schampheleire et al [6]). …”
Section: Porosity -Process Technologies and Applications 182mentioning
confidence: 99%
See 1 more Smart Citation
“…The effective thermal conductivity (k eff ) mentioned here is the property to conduct heat through the multi-compositions within the porous media, which can be calculated based on Fourier's law. Along with theoretical solutions, numerical simulations-by taking into account pore distribution by using computational heat transfer methods-have also been employed to study the heat transfer characteristics of porous material, such as lattice Boltzmann method [10], mean-square displacement method [11], finite volume method [12,13], the volume averaging theory [14], and the shooting method [15]. The determination of effective thermal conductivity is crucial as input data for a number of approaches employed in numerical simulation of heat and fluid flow in porous media, as for instance when the generalized model is employed.…”
Section: Introductionmentioning
confidence: 99%